Meningkatkan Kemandirian Anak Usia 4-5 Tahun Melalui Permainan Busy Book di TK Masjid Al Hikmah: Enhancing the Independence of 4–5-Year-Old Children Through "Busy Book" Games at Al Hikmah Mosque Kindergarten - Delayusvita Delayusvita; Arizka Harisa (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Independence is a developmental aspect that requires stimulation from an early age, as it plays a crucial role in enabling children to perform daily activities without relying on others. However, observations at Masjid Al Hikmah Kindergarten in Central Jakarta revealed that the independence levels of children in Group A were still low. Most children struggled with simple life skills, such as putting on shoes, buttoning clothes, and tidying up toys after use. Consequently, there was a need for engaging, interactive learning media suited to children's developmental characteristics—specifically, the use of "busy books." This study employed Classroom Action Research (CAR) conducted over two cycles, each comprising planning, action implementation, observation, and reflection phases. The subjects were 20 children (aged 4–5) from Group A at Masjid Al Hikmah Kindergarten. Data were collected through observation, interviews, and documentation, then analyzed using both quantitative and qualitative descriptive methods to track improvements in independence across the cycles. The results demonstrated a gradual increase in independence from the pre-action stage through Cycle I and Cycle II. The children showed improved ability to perform various life skills independently, such as putting on shoes, buttoning clothes, and tidying up toys. By the end of Cycle II, the percentage of children achieving independence surpassed the minimum success indicator of 75%. The study concludes that busy books are an effective learning tool for enhancing independence in children aged 4–5. This medium provides an enjoyable learning experience, fosters active engagement, and stimulates life skills appropriate for early childhood development.